Spatiotemporal variation in soil salinity under irrigated fields at Bochessa Catchment in Central Ethiopia - Wendemeneh, D.; Ayana, M.; Haileslassie, Amare; Lohani, T. K. (Wiley, 2024)
Soil salinity and sodicity problems are one of the major challenges to the permanence of irrigated agriculture in Ethiopia. This manuscript, therefore, concerns its spatial and temporal variation under irrigated fields and suggests possible management options. For this investigation, eight monitoring locations were selected based on the irrigation intensity that farmers practised in the area. With each location, three irrigated farmers' fields were randomly selected for sampling purposes. Likewise, six farmers' fields from the rain-fed system were also selected for comparison purposes. Sampling was performed at the beginning and end of each cropping season for three consecutive years from 2017 to 2019. The major physical and chemical properties of the soil were analysed in accordance with standard laboratory procedures. A linear model of two-way analysis of variance was used to analyse parameters across time and space. The results indicated that the majority of the soil properties studied showed significant differences (p < 0.05) over time. This implies that the change is in accordance with the seasonal soil property, possibly due to irrigation practices. Similarly, approximately 90% of the soil properties studied showed noticeable differences (p < 0.05) across locations. Almost all salinity indicators showed an increasing trend in irrigated fields compared to their situation in rain-fed fields. For instance, the electrical conductivity (EC) and exchangeable sodium percentage (ESP) values across the fields ranged from 0.54 to 0.82 dS m−¹ and 8–1%, respectively, with maximum values observed in irrigated fields. This implies that irrigation practices influence soil properties in the area. In addition, the ESP values approaching the maximum permissible limit suggest that sodicity may cause more problems than salinity in the area. Therefore, agronomic practices (e.g. residue management, deep tillage, salt-tolerant crops and periodic fallowing), irrigation and drainage management practices, and amendments may help farmers mitigate salinity and sodicity problems in the area.